Criminal protection of sexual integrity of a person: some problematic aspects (Law and Safety, 2022)
Despite the fact that the criminal law aspects of encroachment on sexual freedom and sexual integrity of a person in modern legal science are developed at a fairly high level, the problems of criminal liability for encroachment on sexual integrity of a person are insufficiently studied in view of significant legislative changes. The article is devoted to the analysis of the concept of “sexual integrity of a person” within the institute of criminal liability for sexual offenses. The terminological shortcomings of this expression are considered, the ways of overcoming such problems are determined. Approaches and concepts for the definition of sexual integrity and its relationship with the concept of sexual freedom have been studied. It has been determined in which cases the use of this term may not be acceptable, and where it is necessary. The content of the terminological appeal has been partially clarified and expanded, the frequently used mistakes of the narrowed use of the analyzed concept have been pointed out. It has been noted that sexual integrity is enjoyed not only by minors under the age of sixteen, but also by persons who, due to their mental or physical disabilities, do not understand the nature and significance of sexual acts committed against them. Based on the study of scientific approaches to the definition of the terminological term “sexual integrity”, a conclusion has been made about the lack of unity among scientists. There is no unanimity on the definition of the relationship between the concepts of “sexual freedom” and “sexual integrity”. It has been established that sexual integrity includes not only a legal but also a moral prohibition to have sexual intercourse with a person who does not have sexual freedom and is unable to decide independently with whom and how to meet their physiological needs. It has been stated that a person who has not reached the “age of sexual consent” is guaranteed to have sexual integrity. When sexual integrity is encroached upon, the normal sexual development of the child is harmed. Thus, sexual integrity is a guarantee of normal sexual development of a minor, because at this age the process of moral and physical development is not yet complete.